Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5888/pcd11.140089
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cardiovascular Risk in Asymptomatic Users of the Primary Health Care Network in Lebanon, 2012–2013

Abstract: IntroductionIn 2012, the Ministry of Public Health in Lebanon piloted a service of multifactorial cardiovascular screening in the publicly subsidized Primary Health Care (PHC) Network. We present an epidemiological analysis of data produced during this pilot to justify the inclusion of this service in the package of essential services offered through PHC and to present a preliminary cardiovascular risk profile in an asymptomatic population.MethodsA total of 4,205 participants (two-thirds of which were women) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…However, the reduction was not clinically meaningful. Baseline BMI in the present study was similar to those reported previously in Lebanon by Yamout et al [31], where 40% were overweight and 30.3% were obese.…”
Section: Discussionsupporting
confidence: 91%
“…However, the reduction was not clinically meaningful. Baseline BMI in the present study was similar to those reported previously in Lebanon by Yamout et al [31], where 40% were overweight and 30.3% were obese.…”
Section: Discussionsupporting
confidence: 91%
“…This is particularly true in light of the expanding role of the private sector [ 24 ]. This has required the health system in Lebanon to adapt to the changing health needs of the population [ 7 , 24 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on secondary analysis of data generated as part of a screening service implemented by the Lebanese Ministry of Public Health in 2012 in 25 primary health care centers distributed over the entire Lebanese territory. The detailed description of the study design, conduct and the preliminary results are reported elsewhere [17]. In brief, the screening served 5,875 beneficiaries and included questions and direct measurements to assess six significant cardiovascular risk factors (random blood sugar (RBS), blood pressure (BP), smoking status, family history of premature CVD, body mass index (BMI), and WC), along with age, sex, education, work status and residence.…”
Section: Study Subjectsmentioning
confidence: 99%